Genetic variants at 8q24 are associated with risk of esophageal squamous cell carcinoma in a Chinese population. Issue 6 (13th April 2014) - Dai, Ningbin; Zheng, Mingfeng; Wang, Cheng; Ji, Yong; Du, Jiangbo; Zhu, Chen; He, Yisha; Zhu, Meng; Zhu, Xun; Sun, Min; Dai, Juncheng; Ma, Hongxia; et al.
<x xml:space="preserve">Abstract</x> Esophageal cancer and gastric cancer have shared risk factors and inherited susceptibility. Recent genome‐wide association studies have identified multiple genetic loci associated with gastric cancer risk, which may also involve in the development of esophageal cancer. Herein, we evaluated the relationship of gastric cancer risk‐related variants at 1q22, 3q13.3, 5p13.1, and 8q24 with the risk of esophageal squamous cell carcinoma (ESCC) in a Chinese population with a case–control study (2139 cases and 2273 controls). We found that the T allele of rs2294008, an intronic variant of the PSCA gene at 8q24 that was previously associated with an increased risk of gastric cancer, was inversely associated with a decreased risk of ESCC (odds ratio = 0.90; 95% confidence interval, 0.81–0.99; P = 0.034). Of interest, the association of rs2294008 with ESCC was consistent with that observed in esophageal adenocarcinoma and ESCC in Caucasian populations. However, no significant associations were observed for the other three variants at 1q22 (rs4072037), 3q13.31 (rs9841504), and 5p13.1 (rs13361707). Our findings suggest that the susceptibility locus of PSCA at 8q24 may be a double‐edged sword, as modulator between the carcinogenesis processes of stomach and esophagus.